Grain Yield Efficiency Of The Drip Irrigation System Of Corn In The Conditions Of Gray Pasture - Yuldoshev Ramazon Khasan ugli; Isayev Sabirjan Khusanbyeviich (Zien Journals, 2024)
This article presents information on the effects of drip irrigation and drip irrigation on the growth, development and productivity, of corn in the conditions of alluvial meadow soils of the Bukhara region
Keywords: Repetitive corn; low salinity; grassland alluvial soils